The genotypic spectrum of ALDH7A1 mutations resulting in pyridoxine dependent epilepsy: A common epileptic encephalopathy. Issue 2 (22nd February 2019) - Coughlin, Curtis R.; Swanson, Michael A.; Spector, Elaine; Meeks, Naomi J. L.; Kronquist, Kathryn E.; Aslamy, Mezhgan; Wempe, Michael F.; van Karnebeek, Clara D. M.; Gospe, Sidney M.; Aziz, Verena G.; Tsai, Becky P.; Gao, Hanlin; et al.
Abstract: Pyridoxine dependent epilepsy (PDE) is a treatable epileptic encephalopathy characterized by a positive response to pharmacologic doses of pyridoxine. Despite seizure control, at least 75% of individuals have intellectual disability and developmental delay. Current treatment paradigms have resulted in improved cognitive outcomes emphasizing the importance of an early diagnosis. As genetic testing is increasingly accepted as first tier testing for epileptic encephalopathies, we aimed to provide a comprehensive overview of ALDH7A1 mutations that cause PDE. The genotypes, ethnic origin and reported gender was collected from 185 subjects with a diagnosis of PDE. The population frequency for the variants in this report and the existing literature were reviewed in the Genome Aggregation Database (gnomAD). Novel variants identified in population databases were also evaluated through in silico prediction software and select variants were over‐expressed in an E.coli ‐based expression system to measure α‐aminoadipic semialdehyde dehydrogenase activity and production of α‐aminoadipic acid. This study adds 47 novel variants to the literature resulting in a total of 165 reported pathogenic variants. Based on this report, in silico predictions, and general population data, we estimate an incidence of approximately 1:64, 352 live births. This report provides a comprehensive overview of known ALDH7A1 mutations that cause PDE, and suggests that PDE may be more common than initially estimated. Due to the relative high frequency of the disease, the likelihood of under‐diagnosis given the wide clinical spectrum and limited awareness among clinicians as well as the cognitive improvement noted with early treatment, newborn screening for PDE may be warranted.